THE RELATIONSHIP BETWEEN LEARNING MOTIVATION, LEARNING FACILITIES AND LEARNING INDEPENDENCE WITH STUDENT RESULT IN MATHEMATIC LEARNING IN CLASS VIII SMP MUHAMMADIYAH PAKEM - Fathiah Umriani; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Low students, the results of learning, are associated with many factors. Learning motivation, learning facilities, and learning independence are factors that have a relationship with the learning results. This study aims to determine whether or not a positive and significant relationship between learning motivation, learning facilities, and independence of learning with the results of learning mathematic students of class VIII SMP Muhammadiyah Pakem Sleman second Semester Teaching Year 2016/2017. The population in this study comprises students of class VIII SMP Muhammadiyah Pakem Sleman District second Semester of the academic year 2016/2017 consisting of 4 classes with a total of 151 students. Random sampling techniques took the experimental class and the sample class to the class. They obtained the trial class VIII A and VIII D as the sample class. The test and questionnaire method do the technique of collecting data. Test the instrument using the validity test, the test of different power, and reliability test. Test prerequisite analysis that is normality test, independent test, and linearity test. Data analysis for hypothesis testing using correlation analysis and linear regression analysis. The results showed that there is a positive and significant relationship between learning motivation, learning facilities, and learning independence with mathematics learning results with Fcount = 6,7209 and Ftable = 2,8826, so that obtained Fcount> Ftable. Coefficient of double correlation (R) equal to 0,6102 and coefficient of determination (R2) equal to 0,3723 with linear regression equation that is Å¶ = 10,1472 + 0,3886X1+ 0,2961X2+ 0,1626X3. Relative contribution X1 that is equal to 59,0770%, X2 equal to 29,3821% and X3 equal to 11,5409% and effective contribution X1 equal to 21,9921%, X2 that is equal to 10,9379% and X3 that is equal to 4,2962%.